Single-Molecule Imaging in Living Drosophila Embryos with Reflected Light-Sheet Microscopy - Greiss, Ferdinand (Biophys J, 2016)
In multicellular organisms, single-fluorophore imaging is obstructed by high background. To achieve a signal/noise ratio conducive to single-molecule imaging, we adapted reflected light-sheet microscopy (RLSM) to image highly opaque late-stage Drosophila embryos. Alignment steps were modified by means of commercially available microprisms attached to standard coverslips. We imaged a member of the septate-junction complex that was used to outline the three-dimensional epidermal structures of Drosophila embryos. Furthermore, we show freely diffusing single 10 kDa Dextran molecules conjugated to one to two Alexa647 dyes inside living embryos. We demonstrate that Dextran diffuses quickly (∼6.4 μm(2)/s) in free space and obeys directional movement within the epidermal tissue (∼0.1 μm(2)/s). Our single-particle-tracking results are supplemented by imaging the endosomal marker Rab5-GFP and by earlier reports on the spreading of morphogens and vesicles in multicellular organisms. The single-molecule results suggest that RLSM will be helpful in studying single molecules or complexes in multicellular organisms.